Socio-demographic status of Children with Autism Spectrum Disorder and their Parents in Dhaka city - Begum, Fardaus Ara; Rahman, Abu Sayem Mirza Md Hasibur; Islam, Md Shafiqul (International Journal of Human and Health Sciences (IJHHS), 2019)
Background: Autism spectrum disorder (ASD) has increased dramatically in the last two decades in the whole world. ASD hampers child’s and their parent’s quality of participation in everyday life. This study examined socio-demographic status of ASD children and their parents in Dhaka city, Bangladesh. Methodology: This is a descriptive type of crosssectional study. Total 44 parents of Autistic children were interviewed, excluding 9 non respondent parents. We collected data by using self-administered questionnaires. Data was analyzed in SPSS-16. Results: Majority (52.3%) ASD children were within 11-15 years, 75% of them had 2-4 siblings and 95.5% of them had no health insurance for themselves or their parents. About parents of ASD children, majority (34.1%) were between 41-50 years old, 90.9% of the participants were mother, 90.9% were married, 79.5% parent lives in a nuclear family, 75% of them were unemployed and most (29.5%) of them are with medium education (HSC). However, male female ratio of ASD children was 2.05:1 in our study. Conclusion:The findings from this study indicated that parents of children with ASD are with medium education. They are unemployed and with no medical insurance either for themselves or for their children. Again, abetter study design is needed in future to collect gender of all selected ASD population. International Journal of Human and Health Sciences Vol. 04 No. 01 January’20 Page : 36-40